Sustainable Career Development of The Senior High School Educators - Milka, Milka (International Research-Based Education Journal, 2019)
This paper aimed to describe how educators explore their career to achieve the goals which have been set beforehand. It also attempted to provide a clear image of different career strategies which have been implemented by the educators at schools. This study used qualitative approach by employing the multi-case study design. Data was analyzed using the constant comparative method. The result indicated some differences were found at the stage of career exploration. Furthermore, at the stage of determination of career goals, the educators had been determined to commit to their organizational or professional growth.Keywords: career development, educators, career exploration, career goals, career strategies.